Manajemen Layanan Laboratorium IPA di Madrasah Aliyah Annuriyyah Jember - Rofiq hidayat; Faizatul Khusniya; Sahawatul Jannah; Siti Khotijah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Laboratories are uniform in terms of management and availability of complete equipment. Attention is needed to manage the laboratory well. More specifically, the science laboratory includes the fields of Biology, Chemistry and Physics. This research aims to find out how science laboratory services are managed at Ma Annuriyyah Jember. The emphasis of this research is how the head of the laboratory carries out management so that the science laboratory services at Ma Annuriyyah Jember can function well in accordance with the observations that will be made. This research uses qualitative research methods with research data collection instruments using interviews, observation and documentation. The results obtained from this research are that the science laboratory service management process at Ma Annuriyyah Jember is carried out well, both from the ongoing science laboratory program planning and the existing science laboratory management structure, at the Ma Annuriyyah school the science laboratory is not only used for practice. Only, but as a classroom where science laboratory learning takes place.